Implementasi Kebijakan Menteri Perdagangan Republik Indonesia Nomor 31 Tahun 2016 Dalam Perspektif Keamanan Lingkungan - Sarai Casandra Yustika Martha Marpaung (Journal of International Relations, 2023)
The state's awareness of increased growth and economic opportunities in the industrial sector encourages the state to take on roles and responsibilities so that the state intervenes in the form of regulations on the imports of non-B3 waste as raw material for the recycling industry. However, as the waste import activities were carried out, many B3 wastes were found to be entering. Researchers see that the problem of importing B3 waste needs to be seen from the point of view of implementing policies that have been formed based on the interests of the state and then finding out to what extent the state plays a role and what the results of this policy is when implemented by the state. Researchers seek to see the implementation of this policy through the role of the state concept and the perspective of Edwards III. Based on the final results, several obstacles were found in the implementation of the non-B3 waste import regulatory policy, therefore  policy did not work as expected.Keywords: the role of the state, policy implementation, imported waste.